PELUANG DAN TANTANGAN PROFESI AKUNTAN DI ERA BIG DATA - afrida putritama (Jurnal Akuntansi, 2019)
Many people worrying about the profession of Accountants no longer needed by the business world in the era of big data because it was replaced by various accounting software that is cheaper, faster and more accurate in noting the financial transactions. The purpose of the writing of this article is to provide an action plan to address the opportunities and challenges of the profession accountant in the era of big data. Research methodology used in this article is literature review. We suggest these following action plan: First, the accountant should improve the skills and competencies of digital to focus on tasks that are more strategically, and not the technical tasks which could be replaced by accounting software; Second, accountants should anticipate the implications of difference in accounting standards and regulations between countries; Third, the association of accounting profession should create policy which encourages the increase of accountants’ skills and competencies in digital field through the obligation of following conferences, workshops, and training for its members; Fourth, the universities should have collaboration with the association of accounting profession to develop a curriculum aligned with the opportunities and challenges of the accounting profession in the era of big data, simultaneously delivering big data analysis training and integrated reporting for civitas academica, while holding a variety of discussion forums to find solutions to the problems of the accounting profession in the era of big data; Fifth, the Government should ensure the creation of stable political conditions, the stock exchange trade actively and publicly share ownership levels are high, and hit the number of bribery corruption also so that the accountant can develop optimally in the era of the big the data.